Comparison of New Approaches of Semi-syllable Units for Speech Recognition of Any Arabic Word. Issue 1 (1st September 2022) - Boumehdi, Ahmed; Yousfi, Abdellah
Abstract: This study uses the same semi-syllable units already defined in our previous work; a semi-syllable is a simple Arabic letter followed by its diacritic information. This work experiment with three configurations. In the first configuration, we redefine the "السكون" (Soukoun is an Arabic diacritical sign representing the absence of a vowel) as a new independent phonemes that is different from the consonant itself. In the second configuration, we also redefine the geminated consonant with a new independent phoneme. In the last configuration, we combined the first two experiments. The results proved that the three configurations gave better results compared to regular semi-syllables, and the highest recognition rate was achieved on the third configuration.